Argentometric chloride determination by inductively coupled plasma-optical emission spectroscopy in a wide range of sample matrices. Issue 12 (9th March 2023) - Lerner, Nadav; Avraham, Hanan; Leffler, Nitai; Weinstock, Ira A.; Zeiri, Offer
Abstract : An argentometric method has been developed, allowing sensitive chloride determination in a wide variety of matrices using any ICP-OES instrument. Abstract : Chloride determination is of great importance, as chloride plays important roles in human health, pitting corrosion, environmental processes, and agriculture. However, chloride determination by inductively coupled plasma-optical emission spectroscopy (ICP-OES), one of the premier techniques used for elemental analysis, is currently limited to specific instrument types or requires the use of additional equipment. This work presents an argentometric method for the indirect measurement of chloride, applicable to any ICP-OES instrument. The initial Ag + concentration added to samples is of great importance, as it affects both the method's limit of quantification (LOQ) and the top limit of its working range. The developed method found 50 mg L −1 of Ag + to be the optimal concentration, providing a working range of 0.2–15 mg L −1 Cl − . The method was robust to changes in filtration time, temperature, and sample acidity. Using the argentometric method, chloride was determined in a variety of samples (spiked-purified water, seawater, wine, and urine). For validation, the results were compared to those obtained using ion chromatography and showed no statistical differences. Argentometric chloride determination by ICP-OES is therefore applicable to many types of samples and can be easily performed on any ICP-OES instrument.